Measuring The impact of Investment Expenditures on the GDP outside the hydrocarbon sector in Algeria using the ARDL model for the period 2000-2020 - djorfi, Zakaria; benmerzoug, nabil (Journal of Research in Finance and Accounting, 2022)
In light of the financial surpluses that it achieved as a result of the high oil prices, Algeria proceeded to generalize a long-run strategy through the application of an expansionary policy aimed at reviving investment dynamism in a way that would ensure the revival of macroeconomic indicators and work to raise the absorptive efficiency of the Algerian economy. Therefore, this study aims to determine the short and long-run relationship between Investment Expenditures and the gross domestic product outside the hydrocarbon sector during the period 2000-2020, using the ARDL model, and the econometric study concluded that there is a short and long-run equilibrium relationship, in addition to the absence of a problem of autocorrelation to sequence errors with stability of estimations over time.